Heterotopic ossification in psammomatous spinal meningioma: a diagnostic controversy - Wong, Yin Ping (Int J Clin Exp Pathol, 2021)
Heterotopic ossification (HO), a synonym for osseous metaplasia, is a pathological phenomenon, characterized by abnormal bone formation outside the skeletal system observed commonly in various neoplastic and non-neoplastic diseases. HO occurring in meningioma is exceptionally rare. We reportherein an unusual case of spinal meningioma containing numerous calcified psammoma bodies and extensive HO in a 75-year-old woman, who presented with progressive worsening bilateral lower limb weakness and numbness. The presence of remarkable bone formation within a meningioma is controversial among pathologists; while some regard them as psammomatous meningioma as the primary diagnosis, others prefer osteoblastic meningioma, a form of metaplastic meningioma. There is compelling molecular data to advocate that HO is an active disease process involving metaplastic (osseous) differentiation of meningioma stroma mesenchymal stem-like cells, but not the meningothelial-derived tumor cells. Henceforth, the term “metaplastic meningioma” may not be appropriate in this context. A plausible designation as “psammomatous meningioma with osseous metaplasia” defines this entity more accurately. This paper highlights the need for a unifying nomenclature to reduce diagnostic controversy caused by conflicting terms in the literature. The possible pathogenesis of this intriguing phenomenon is discussed.